Exploring the Canggu-Bali Magnet as a Choice for Digital Nomads - Pipin Oktapiani, Ni Made; Putu Mahyuni, Luh (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Tourism is a leading sector worldwide, but the Covid-19 pandemic has had a significant impact on various aspects of life around the world. Over time, tourism in Bali has now gained popularity and become a favorite tourist destination for tourists, especially digital nomad tourists. The purpose of this study was to explore the perceptions and review in more depth the intentions of digital nomad tourists to work from Canggu-Bali. The research design used in this study is a qualitative method with a phenomenological approach. The results of this study show that Canggu has become a magnet for digital nomads around the world. With a unique combination of natural beauty, rich local culture. Digital nomads who choose to work from Canggu experience a significant increase in their quality of life. Factors such as access to comfortable co-working spaces, refreshing tropical weather, and a healthy lifestyle and outdoor activities, make Canggu more than just a place to work, but also a place to find balance between work and personal life.